2019
DOI: 10.22158/selt.v7n1p75
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perceptions of MALL in EFL Classes

Abstract: <p><em>Mobile technologies are rapidly attracting new users, providing increasing capacity, and allowing more sophisticated use</em><em> such as accessing the Internet for searching information, emailing and reading e-books. As the mobile technology has been more powerful and inclusive in people’s daily lives, the issue of mobile assisted language learning (MALL) has also been widely studied. Many researchers of MALL consider the emerging mobile technologies to have potential for the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…The limitations of this article consist in a small sample of the respondents, as well as in the use of only one survey method. However, the results comply with the findings of other research studies on this topic [3,6,7,13,14,16,37].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The limitations of this article consist in a small sample of the respondents, as well as in the use of only one survey method. However, the results comply with the findings of other research studies on this topic [3,6,7,13,14,16,37].…”
Section: Resultssupporting
confidence: 91%
“…They reported that it had been more fun, less stressful, easy to use, and a better way to learn than from the textbooks. This is in line with a research study by Kwangsawad [13] and Elaish et al [19], who reported that their students also had found using smartphones in EFL classes more fun, beneficial and productive. Similar findings were provided by Deris and Shukor [14].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…From the interview of the students, there is a few of them that have old fashion mobile phone, so they often get trouble in using it. Those are similar to the issues that shown in the journal written by Kangsawad (2019). Other technological problems and difficulties in mobile learning include technical problems of operating the device.…”
Section: Improving Students' Skillssupporting
confidence: 56%
“…MALL is different from CALL (Computer Assisted Language Learning) in its use of personal, portable device that can be carry out in any places, and its spontaneity of use. Among all kinds of technology that available nowadays, mobile phones are the most popular ones and outnumber personal computers, and they have an important place particularly in young generation (Kwangsawad, 2019).…”
Section: Introductionmentioning
confidence: 99%